Stabat Mater, by Janaina Leite: scenic autofiction inverting moral violence: (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article sought to analyse the play Stabat Mater, by Janaina Leite, from the concepts of performative persona and scenic autofiction, in order to show how its dramaturgy inverts the power of the obscene and promotes a scene that questions to what extent a symbolic action can generate consequences and real actions. To this end, Leite structures a rhapsodic, ambiguous and poetic scene, which mixes figures and themes a priori incompatible with motherhood and pornography. In addition to the concepts already mentioned, others by Foucault and Butler were evoked to think about the performative persona in Stabat Mater as an image of the violent (and obscene) morality born of the crisis of ethical thinking about oneself and about the other.
Keywords: Stabat Mater; scenic autofiction; contemporary theater; performative persona; parrhesia